Long Memory in the Energy Consumption by Source of the United States: Fractional Integration, Seasonality Effect and Structural Breaks - Adekoya, Oluwasegun B. (Estudios de Economía, 2020)
In this paper, long memory behavior of the energy consumption by source of the United States has been examined using the fractional integration technique for the three conventional cases of no regressors, an intercept, and an intercept and a linear trend. In addition, this study extends majority of past studies by considering the effects of seasonality and structural breaks. Using monthly data, it is found that across all the sources considered, energy consumption exhibits long memory with the degree of persistence largely ranging between 0 and 1. Also, the estimated results of the models with seasonality effect and structural breaks show that the energy consumption series have significantly strong seasonal pattern and autoregressive components, and the presence of structural breaks significantly alter the degree of persistence of most of the energy sources. The reports of this study have serious policy implications in the aspect of energy consumption mix, energy consumption efficiency and environmental concerns